United Republic of Tanzania : Third Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for United Republic of Tanzania. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper reviews Tanzania's economic performance under the program supported by the Policy Support Instrument. Macroeconomic performance of Tanzania remains broadly favorable. Quarterly accounts indicate that real GDP grew by 7.2 percent in the first half of 2015, driven by construction, transport, communication, and financial services. The new government that came into power in October 2015 is also committed to further strengthen the economy of Tanzania, although program implementation slowed significantly ahead of presidential election. Revenue and financing shortfalls, together with weak commitment controls, led to the accumulation of further domestic arrears. At 3.3 percent of GDP, the fiscal cash deficit for 2014/15 was below the programmed 3.8 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet